KAJIAN LITERATUR ENDOWMENT EFFECT, LOSS AVERSION DAN STATUS QUO BIAS DALAM PENGAMBILAN KEPUTUSAN - Bayu Laksma Pradana (Jurnal Bina Manajemen, 2020)
This paper explains Endowment Effect, Loss Aversion and Status Quo Bias as part of anomalies that Kahneman explained. Endowment effect results as people tend value something more precious when they own the good. Loss Aversion, when people put weight on losing higher than winning. Status Quo Bias, people tendency to stick on default option rather than finding other options. It also provides with evidence and experimental research that had been conducted by researcher focusing in the field of the study. Some examples also discussed to broadening the understanding in the topic